Immunofluorescence examination of beta tubulin expression and marginal band formation in developing chicken erythroblasts (The Rockefeller University Press, 1986)
Chicken erythrocyte beta tubulin, a tubulin variant with unique biochemical and assembly properties, is found to be specifically contained in two chicken blood cell types--erythrocytes and thrombocytes. The beta tubulin variant is absent or present in low amounts in a variety of white blood cell types and other body tissues, as determined by immunofluorescence microscopy and a semi-quantitative immunoblotting procedure. During differentiation in the marrow the beta tubulin variant appears suddenly in mid-stage erythroblasts at the onset of hemoglobin synthesis, and forming marginal bands are seen in all subsequent polychromatophilic erythroblast stages. The developmental sequence of events in marginal band formation entails microtubule nucleation at the centrosome, followed by microtubule elongation, consolidation of loose parallel microtubules into a compact bundle, and microtubule association with the cell membrane.